In vitro metabolic stability and biotransformation of isosteviol in human and rat liver fractions. Issue 3 (June 2019) - Adehin, Ayorinde; Tan, Keai Sinn; Lu, Zhiqiang; Cheng, Qing; Tan, Wen
Abstract: Isosteviol is a lead compound whose cardioprotective property has been partly explained by its regulation of ion channels and interference with signalling pathways in the metabolism of some fatty acids. This study determined the metabolic stability of isosteviol in human liver microsomes and H9c2 cell line, and the identity of its metabolites in human and rat liver fractions. Isosteviol was largely unmetabolized in H9c2 cells and in NADPH-only supplemented human liver fractions, suggesting a very limited contribution of phase I biotransformation to its hepatic clearance. The in vitro half-life of isosteviol in UDPGA-only supplemented medium was observed to be 24.9 min with an estimated intrinsic clearance of 0.349 mL/min/kg in man. Analysis by LC-MS/MS and Q-tof showed that isosteviol is mainly metabolised to its acyl-β-D-glucuronide in humans and rats. Mono-hydroxy-isosteviol and dihydroisosteviol were also identified. Rat liver fraction, however, generated dihydroxy-isosteviol in addition to two mono-hydroxy derivatives. Further studies confirmed that dihydroisosteviol is subsequently biotransformed to its acyl-β-D-glucuronide in man and rat. These findings suggest that future studies of the efficacy and toxicity of isosteviol might have to consider xenobiotics that alter the glucuronidation pathways significantly in man. Graphical abstract: Image 1